IMPLEMENTASI GANJARAN DAN HUKUMAN DALAM PROSES PEMBELAJARAN DI MTS AL-BANNA PULAU BANYAK KECAMATAN TANJUNG PURA-LANGKAT - Nurmisda ramayani (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
Abstract: Humans have the ability to think that is still in the form of potential, then become actualthrough al-ta’lim and al-riyâa’h in accordance with its physical and mental development, the outsideworld that is affected and programmed and even planned will be able to optimize human potential betterIn the future. The ability of human thinking will emerge in actuality after humans have the ability tamyiz(ability to distinguish) between good and bad to do, because people will think that the results of what hehas done will be in accordance with the process or business. Man’s tamyiz ability can encourage people todo positive things through education, many factors are considered in achieving educational goals, such asalways pay attention to the methods of education applied in schools, because it will affect and facilitate theproviders of education To be more effective and efficient in achieving goals. Among them are the applicationof rewards and punishments in the learning process, this is one of the many teaching methods ineducation. The application of both methods is often misunderstood by educational practitioners, even iflinked to the jurisprudence laws there will be a judge that the world of Islamic education is seen as thosewho impose military discipline and apply harsh punishment. In fact it is not so, Imam Al-Ghazali includingone of the figures who fight for the elimination of harsh punishment against learners. This study aims tofind and know how the views of Islamic education leaders about punishment and reward, to know howthe implementation of rewards in the learning process at school, the execution of punishment in thelearning process at school, what are the constraints faced in implementing the rewards and punishmentsin the learning process in school, and what are the solutions to the constraints faced in implementing therewards and punishments in the learning process in school.